2022
DOI: 10.1111/nuf.12833
|View full text |Cite
|
Sign up to set email alerts
|

Physical problems and fatigue level of nurses during the COVID‐19 pandemic

Abstract: Purpose This study was conducted to examine the physical problems and fatigue levels experienced by nurses during the COVID‐19 pandemic. Method A descriptive and correlational design was used. The study data were collected in a state and a university hospital in the center of this province between September and December 2020. The population of the study included 460 nurses in these two hospitals, and the sample consisted of 377 volunteer nurses, which represented 81.95% of the population. Data collection tools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies have indicated that nurses' physical and emotional distress is compounded by uncertainty, fear of infection, work overload and ethical dilemmas (Fernandez et al, 2020;Koh et al, 2011). Nurses have reported dermatitis, headache, dehydration, discomfort, general body pain, giddiness and excessive sweating caused by the prolonged wearing of personal protective equipment (PPE) (Erdaği Oral et al, 2022;Jose et al, 2021). These may have impacted on nurses' ability to deliver safe and effective person-centred care.…”
Section: Sars-cov-2 Is a Severe Viral Respiratory Pandemic That Causesmentioning
confidence: 99%
“…Studies have indicated that nurses' physical and emotional distress is compounded by uncertainty, fear of infection, work overload and ethical dilemmas (Fernandez et al, 2020;Koh et al, 2011). Nurses have reported dermatitis, headache, dehydration, discomfort, general body pain, giddiness and excessive sweating caused by the prolonged wearing of personal protective equipment (PPE) (Erdaği Oral et al, 2022;Jose et al, 2021). These may have impacted on nurses' ability to deliver safe and effective person-centred care.…”
Section: Sars-cov-2 Is a Severe Viral Respiratory Pandemic That Causesmentioning
confidence: 99%